A Pediatric Case of Relapsing-Remitting Multiple Sclerosis Onset following Varicella Zoster Ophthalmicus with Optic Neuritis - Naoko Shiba; Yuji Inaba; Mitsuo Motobayashi; Makoto Nishioka; Yoichiro Kawasaki; Shunsuke Noda; Hiroki Matsuura; Norimoto Kobayashi; Takafumi Matsuoka; Akinori Nakamura; Yozo Nakazawa (Case Reports in Pediatrics)
Some epidemiological studies have implied a pathogenetic association between varicella zoster virus (VZV) and multiple sclerosis (MS); this, however, remains controversial. The present report describes a case involving an immunocompetent 10-year-old girl who developed relapsing-remitting MS following the prolonged reactivation of VZV inside the first branch of the trigeminal nerve, exhibiting herpes zoster ophthalmicus with severe optic neuritis. Symptoms related to herpes zoster ophthalmicus and MS appeared consecutively in the 10-week period after the appearance of vesicles. This suggests that the onset of MS was triggered by some mechanism involving VZV reactivation in the first branch of the trigeminal nerve. To the best of our knowledge, this report is the first to describe a relationship between the onset of MS and herpes zoster ophthalmicus. Early diagnosis and aggressive antiviral therapy are important in cases of herpes zoster ophthalmicus to prevent the possible development of MS as well as visual impairment as sequela.